A tradição polícroma da Amazônia no contexto do Médio Rio Solimões (AM) - Lopes, Rafael Cardoso de Almeida (2018)
This dissertation has the purpose of producing a regional history of the occupations of the producers of the pottery associated with the Amazonian Polychrome Tradition (TPA) in the area of the middle Solimões River. The case study of this research is the excavation and ceramic analysis of the São João site, near Lake Caiambé (Tefé-AM). To complete the objective the form and validity of the production of regional long-term indigenous histories will be discussed, a theoretical choice that will prioritize, in turn, the identification and analysis of past choices accumulated in the archaeological record and in the pottery remains. To size the scope of the research a literature review will present studies about the “TPA” category and about the archaeology and ethno-history of the Middle Solimões. The excavation and ceramic analysis of the São João site allowed a glimpse to the various forms that the producers of TPA occupied the landscape of the Solimoes River. The site and its ceramic analysis served as basis for the reinterpretation of the archaeology of the Middle Solimões and for the production of the regional history of these communities. The accumulated data led to the interpretation that this history is marked by the formation of interaction mosaics between ceramist groups.